2005
DOI: 10.1111/j.1440-1819.2005.01429.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of a brief screening instrument for depression and suicidal ideation for elderly: the Depression and Suicide Screen

Abstract: The early detection of depression and suicidal ideation is essential for the prevention of suicide in the community. This study therefore aimed to develop a brief screen for depression and suicidal ideation that can be easily administered in primary-care settings. The Self-rating Depression Scale (SDS), the Hospital Anxiety and Depression Scale (HADS) and a modified version of the Composite International Diagnostic Interview (CIDI) were administered by 353 residents of a single community aged 64 years and over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 14 publications
(10 reference statements)
2
44
1
Order By: Relevance
“…Another population-based study in Japan targeting people over the age of 64 reported that prevalence of those who scored more than 5 in GDS-15 was 23.8%, which is compatible to our data [26]. …”
Section: Discussionsupporting
confidence: 92%
“…Another population-based study in Japan targeting people over the age of 64 reported that prevalence of those who scored more than 5 in GDS-15 was 23.8%, which is compatible to our data [26]. …”
Section: Discussionsupporting
confidence: 92%
“…Positive predictive values for detecting suicide ideation, although relatively low, were consistent with those reported in the literature about screening for late-life suicide ideation. 44,45 The study group was predominantly white and relatively well-educated for an older cohort; findings may not generalize to other groups. The internal consistency of the GDS-SI was acceptable and may have been limited somewhat by the small number of items in this subscale.…”
Section: Discussionmentioning
confidence: 97%
“…Fujisawa et al . () reported 23.8% depressed older people defined with the GDS‐15 in a provincial community (146 men and 236 women). Aihara et al .…”
Section: Discussionmentioning
confidence: 99%